Perancangan Implementasi Sistem Informasi Penjualan Buku Berbasis Website Menggunakan PHP MYSQL Dengan Framework Codeigniter 4 Dan Boostrap 5 - Hidayat, Atep; Syaahid Albanna, Muhammad (Jurnal Sistem Informasi Galuh, 2025)
Rapid technological advances have made information systems in companies transition from conventional to digital. An easy and fast information system is needed for companies to convey company information, including sales information systems. As is the case with the publisher ProPublic.info. So far, the publisher ProPublic.info does not have digital media to convey company information, including in the book sales information system it publishes. Therefore, this research was created with the aim of creating a website- based book sales information system at the ProPublic publishing company. From this problem, the idea was born to create research with the title "DESIGN and IMPLEMENTATION OF A BOOK SALES INFORMATION SYSTEM BASED ON A PHP MYSQL WEBSITE WITH FRAMEWORK CODEIGNITER 4 and BOOSTRAP 5 ". In this research there is information about the publishing company ProPublic.info and its sales information system.